Review of Grossman and Helpman's Special Interest Politics - Baron, David P (Journal of Economic Literature, 2002)
In Special Interest Politics Gene Grossman and Elhanan Helpman examine how special-interest groups influence political outcomes for the benefit of their members. The authors take interest groups seriously by considering a range of theories and supporting evidence on interest group activity. Their book provides perspectives on how to study interest group politics and a set of methods for that study. Although the authors present a number of standard models, the book contains much that is new. The reader takes away a multitude of results, tools, models, and new research ideas. The result is an outstanding book full of insight, useful methods, and perspective.